2018
DOI: 10.1097/meg.0000000000001192
|View full text |Cite
|
Sign up to set email alerts
|

Outcome and adverse events in patients with chronic hepatitis C treated with direct-acting antivirals: a clinical randomized study

Abstract: We found no difference in AEs possibly related to the DAA regimen in patients with CHC, but surprisingly, AEs possibly related to the DAA regimen persisted in a significant number of patients after treatment. This finding can be of importance for clinicians in relation to patient information concerning AEs possibly related to DAA treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 46 publications
1
15
1
Order By: Relevance
“…SVR was high (98.1%), with no significant differences between groups, in agreement with other Brazilian studies that found an SVR of 91.6‐95% . International studies also showed high rates of response to treatment, ranging from 78.6‐90%, depending on the treatment regimen used …”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…SVR was high (98.1%), with no significant differences between groups, in agreement with other Brazilian studies that found an SVR of 91.6‐95% . International studies also showed high rates of response to treatment, ranging from 78.6‐90%, depending on the treatment regimen used …”
Section: Discussionsupporting
confidence: 89%
“…2,7,20,21 The occurrence of at least one adverse reaction during treatment was reported by 83.2% of the patients, and the most frequently identified ADRs were fatigue, anemia, and headache. Solund et al (2018) found that 97% of patients had an ADR, a higher proportion than that found in our study. However, the most common adverse reactions were anemia (78%), fatigue (74%), and headache (46%).…”
Section: Discussioncontrasting
confidence: 83%
See 1 more Smart Citation
“…In vitro testing is required for characterization of RASs. In constrast to enzyme and replicon assays, infectious HCV culture systems allow investigation of the complete genome and viral life cycle, and results obtained in such systems reflect in vivo data …”
Section: Discussionmentioning
confidence: 99%
“…Serum or plasma from genotype 1a–infected patients with DAA treatment failure and acquisition of 156‐RASs were obtained from the European Resistance Database at the Department of Internal Medicine 1, University Hospital Frankfurt/German Center for Infection Research, External Partner Site Frankfurt, Germany (patients A, B, D, and E), and the National Reference Center for Viral Hepatitis B, C and D, Department of Virology, Henri Mondor Hospital, Créteil, France (patient C). Treatment‐naïve patients were followed at Copenhagen University Hospital, Hvidovre . The study was conducted in accordance with the Declaration of Helsinki, and approval for the use of patient blood samples and retrospective collection of data for research purposes was obtained from the local ethics committees.…”
Section: Methodsmentioning
confidence: 99%